Delayed prescribing of antibiotics for respiratory tract infections: Use of information leaflets - DARKER, CATHERINE (My University, 2013)
The appropriate prescribing of antibiotics is a challenge in primary care. We performed an interventional trial to determine if providing an information leaflet on antibiotics with a delayed antibiotic prescription influenced the patient's decision to use the antibiotic for a respiratory tract infection (RTI). The control group (n=69) where given a delayed prescription and the intervention group (n=46) were given an information leaflet on antibiotics with the delayed prescription. In the control group, 72% (n=50) of patients indicated they subsequently used the antibiotic, and in the intervention group, 43%(n=20) indicated they used the antibiotic, this difference was statistically significant (p = 0.0018.) The key conclusion of this study is that delayed prescriptions should be issued with an appropriate information sheet.
PUBLISHED
Keywords: antibiotic agent